2019
DOI: 10.3367/ufne.2019.01.038520
|View full text |Cite
|
Sign up to set email alerts
|

Experimental studies of two-dimensional complex plasma crystals: waves and instabilities

Abstract: A review of experimental studies on waves, phonon dispersion relations, and mode-coupling instability in two-dimensional complex plasma crystals is presented. An improved imaging method allowing simultaneous measurements of the three wave modes (compression in-plane, shear in-plane, and out-of-plane) is given. This method is used to evidence the formation of hybrid modes and the triggering of the mode-coupling instability due to wake-mediated interactions. The main stages of the mode-coupling instability are a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 96 publications
0
16
0
Order By: Relevance
“…crystalline and fluid MCI, thermoacoustic instability, and thermal explosion) had to be studied separately. We recently demonstrated [23,24,26] that such instabilities can serve as model systems to study thermoacoustic behaviour in chemically-reactive media and flame fronts. Here, we show for the first time that combined instabilities (crystalline MCI -fluid MCI -thermoacoustic instability -thermal explosion) create conditions for thermal activation of heavier particles, which can exhibit behaviour of thermal defects, providing physical analogy with double-step exothermic chemical reactions (reactions with pre-equilibrium).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…crystalline and fluid MCI, thermoacoustic instability, and thermal explosion) had to be studied separately. We recently demonstrated [23,24,26] that such instabilities can serve as model systems to study thermoacoustic behaviour in chemically-reactive media and flame fronts. Here, we show for the first time that combined instabilities (crystalline MCI -fluid MCI -thermoacoustic instability -thermal explosion) create conditions for thermal activation of heavier particles, which can exhibit behaviour of thermal defects, providing physical analogy with double-step exothermic chemical reactions (reactions with pre-equilibrium).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that, under weak damping conditions, plasma wakes can induce mode-coupling instability (MCI) in plasma crystals [24,33,34] and fluids [35], when the energy of plasma flow is transferred to the microparticle subsystem if the in-and out-of-plane collective modes intersect. The crystalline MCI was used in these experiments to initiate the melting of the crystal: once the crystal is intensively heated due to the crystalline MCI ("ignited") in the central (densest) part, radially-expanding front of nonequilibrium melting (flame front, Fig.…”
Section: Sound-induced Activation Of Thermal Defectsmentioning
confidence: 99%
See 1 more Smart Citation
“…The propagation of intense laser pulses in plasma with a wide range of their applications is an interesting area of research. The propagation of intense laser pulse in plasma leads to numerous instabilities and non‐linear effects including, Raman and Brillouin instabilities, modulational and filamentational instabilities, laser self‐focusing, and self‐modulation properties . Furthermore, these processes play a significant role in advanced physical events such as, laser fusion, X‐ray lasers, laser ablation, inertial confinement fusion (ICF), and optical harmonic generation .…”
Section: Introductionmentioning
confidence: 99%
“…In order to observe mode anticrossing directly, we performed dedicated experiments with 2D system of charged microparticles in the same manner as described previously. [32][33][34][35][36] To prepare the fluid, we melted 2D complex plasma crystal utilising the mode-coupling instability [36][37][38] (see details in SI 31 ), however, the same could be done using laser heating. 39,40 First, the model fluid system was set up.…”
mentioning
confidence: 99%